SYSTEM OF ATTRACTING INVESTMENTS IN THE KALUGA REGION ECONOMY - Ivan V. Kostin (Статистика и экономика, 2016)
This article describes the main conditions and factors which allowed regional authorities to create an effective system of the attraction of foreign investments. Besides, the author notes the disadvantages of regional authorities’ investment policy and proves the need of their removal.